Application of intraoperative electrophysiological monitoring in vertebral canal decompression surgery for acute spinal cord injury. Issue 6 (June 2020) - Li, Qun-Xi; Zhao, Xiao-Jing; Li, Xiang-Nan; Fu, Ai-Jun; Zhang, Yun-He; Chen, Tong; Liu, Tie-Jun; Zheng, Fu-Xia; Li, Jian-Min
Objective: This study aimed to evaluate the joint monitoring of somatosensory evoked potentials (SEPs) and motor evoked potentials (MEPs) in vertebral canal decompression surgery for acute spinal cord injury. Methods: Twenty-four patients, who were admitted to the hospital for the surgical treatment of spinal cord injury with SEP and MEP monitoring, were assigned to the intraoperative monitoring group (group I). In addition, 24 patients who were admitted to the hospital for the surgical treatment of spinal cord injury without SEP or MEP monitoring were assigned to the control group (group C). Results: In group I, there were significant changes before and after decompression surgery in the P40 latency and amplitude, and in the latency of MEP in the abductor hallucis brevis (AHB), in patients with improved spinal nerve function following surgery. In contrast, there were no significant differences in the P40 latency or amplitude, or the latency of MEP in the AHB, in patients who showed no improvement after surgery. Conclusion: In vertebral canal decompression surgery for acute spinal cord injury, the application of joint MEP and SEP monitoring can timely reflect changes in spinal cord function.